Non-standard vernaculars in education. (5th February 2014) - Todd, Loreto
Abstract : Even before one opens this book, a potential reader is impressed by the suggested coverage and by the quality of the authors, two of whom are very well known in the fields of creolistics, education and linguistics. A closer survey confirms the coverage, revealing a listing and categorisation of 1626 (p. xviii) or 1624 (p. xix) texts written over the last fifty years and covering.